THE EFFECT OF FIELD EXPERIENCE PROGRAM AND TEACHER PROFESSIONAL PERCEPTIONS ON INTEREST TO BECOME TEACHER WITH SELF-EFFICIENCY MEDIATION - Rindah Suharti; Unggul Purwohedi; Dwi Kismayanti Respati (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to determine the effect of the Field Experience Program (PPL) and the perception of the teaching profession on the interest in becoming a teacher through self-efficacy. The sample size was calculated using data from 201 of the 452 students in the Educational Study Program at the Faculty of Economics, UNJ, in 2017 and 2018. The PPL variable uses secondary data, namely the PPL value. Meanwhile, the variables of professional perception, self-efficacy, and interest in being a teacher used primary data derived from the researcher's questionnaire distribution results. This type of research is quantitative with a survey method. This study's results indicate no influence between PPL and interest in becoming a teacher. There is a positive and significant influence. Self-efficacy in teaching is influenced by exposure to PPL and how one views the teaching profession; this effect was both positive and statistically significant. And self-efficacy mediates between the Field Experience Program (PPL) and the perception of the teaching profession on interest in becoming a teacher.